2010
DOI: 10.1177/0020764010374419
|View full text |Cite
|
Sign up to set email alerts
|

Effects of psychiatric training on nursing students’ attitudes towards people with mental illness in Japan

Abstract: The students' attitudes may change favourably owing to, at least in part, psychiatric training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 26 publications
0
14
0
1
Order By: Relevance
“…Other studies of clinical practice in mental health showed decreased anxiety and greater confidence in learning (Happell ; Yamauchi et al . ). In these studies, clinical experiences were scheduled in the second or third year of the nursing curriculum.…”
Section: Introductionmentioning
confidence: 97%
“…Other studies of clinical practice in mental health showed decreased anxiety and greater confidence in learning (Happell ; Yamauchi et al . ). In these studies, clinical experiences were scheduled in the second or third year of the nursing curriculum.…”
Section: Introductionmentioning
confidence: 97%
“…Students that have direct contact with people with mental health problems regard it as highly beneficial, as the experience gives them a better understanding of the educational interventions and the attitude necessary for delivering adequate health care. All this facilitates a shift towards a more positive attitude in nursing students, with a greater predisposition towards, and a less apprehensive view of, mental health …”
Section: Introductionmentioning
confidence: 99%
“…Hence, it seems imperative to make necessary changes to the existing nursing curriculum. This would help improve the attitude of the nursing students toward psychiatry 18 .…”
Section: Discussionmentioning
confidence: 99%